Just trust me and you'll make a fortune – relationships between offenders and victims of human trafficking. Issue 2 (3rd July 2019) - Viuhko, Minna
ABSTRACT: Despite the increasing amount of research on human trafficking, certain aspects of the phenomenon have remained less studied. For many years, research had focused on trafficking for sexual exploitation and men-exploiting-women cases. Recently, the body of literature has become more diverse, and different forms of trafficking have been recognised. However, the trafficking research has largely ignored the notion of intersectionality, although intersectionality has been applied in several studies, for example, on domestic violence. This article deals with the relationships between offenders and trafficked persons. The study asks what is the nature of the relationships between them. Furthermore, the intersectional approach is applied to analyse what factors make trafficked persons prone to exploitation and, on the other hand, keep them in the exploitative situation. The study also focuses on the power relations between the parties involved. The data consists of trafficking in human beings court judgments from the Finnish courts. The intersectional analysis focuses particularly on the close reading of two cases. The analysis shows that many intersecting factors are linked to the victimisation of trafficked persons. Furthermore, the exploitative relationships between offenders and trafficked persons display many features of unequal distribution of power.